From wastes to health and wealth: a novel halal and healthy jam product from watermelon fruit wastes - A. Mohamad Al-Batt’hi, Souad; Saheed, Olorunnisola Kola; Jamal, Parveen (2012)
Wat materials remained one of the important food grade agro-wastes generated by most hospitality industries in Malaysia. These wastes mostly fleshy rinds are normally discarded. Based on the concept of waste to wealth, Jam was prepared from watermelon rind with different flavours (vanilla, pineapple, strawberry, lemon and no flavour). Five different samples were prepared at various compositions T1 (50-50), T2 (80-20), T3 (60-40), T4 (40-60) and T5 (20-80) of rind and sugar. T1 (50-50) gave the best jam set. Ten man panel (trained) evaluated the jam for its sensory characteristics. Sensory evaluation conducted among five flavours was significantly different at (p>0.05). Chemical analysis showed that ascorbic acid reduced greatly among all treatments during three month storage. Soluble sugar and pH also decreased gradually; for T1 (from 4.96 to 4.40), T2 (from 4.92 to 4.21), T3 (from 4.74 to 4.11), T4 (from 4.62 to 4.51) and T5 (from 4.52 to 4.25). Strawberry flavoured jam was most acceptable.